2002
DOI: 10.1002/ijc.10708
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple HPV infection on response to treatment and survival in patients receiving radical radiotherapy for cervical cancer

Abstract: To obtain information on the incidence and the clinical significance of infection with various types of the human papillomavirus (HPV) in cancer of the uterine cervix, we retrospectively examined the HPV status of 106 patients who had received radical radiotherapy for cervical cancer stages IB to IIIB. DNA was extracted from formalin-fixed, paraffinembedded biopsies and PCR was carried out to identify HPV types 16, 18, 31, 35, 33 and 45. To detect additional HPV types, consensus PCR products were cloned and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
4
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 43 publications
8
69
4
2
Order By: Relevance
“…However, no significance was found between HPV infection and clinicopathological variables, which is consistent with the study by Bachtiary et al (36). The association between HPV and the four biomarkers was also analyzed and only the serum levels of HGF in HPV-positive patients were higher than HPV-negative patients.…”
Section: ------------------------------------------------------------supporting
confidence: 87%
“…However, no significance was found between HPV infection and clinicopathological variables, which is consistent with the study by Bachtiary et al (36). The association between HPV and the four biomarkers was also analyzed and only the serum levels of HGF in HPV-positive patients were higher than HPV-negative patients.…”
Section: ------------------------------------------------------------supporting
confidence: 87%
“…Выявленная одними авторами корреляция содержания HIF-1a со стадией заболевания не подтверждается работами других авторов [24,69,72,73]. Некоторыми авторами также сообщается об отсутствии достоверной взаимосвязи HIF-1a с размером опухоли и статусом лимфоузлов [69][70][71][72][73], что не позволяет однозначно судить о роли HIF-1a в метастазировании РШМ.…”
Section: транскрипционные факторы: фактор индуцированный гипоксией-1unclassified
“…Выявленная одними авторами корреляция содержания HIF-1a со стадией заболевания не подтверждается работами других авторов [24,69,72,73]. Некоторыми авторами также сообщается об отсутствии достоверной взаимосвязи HIF-1a с размером опухоли и статусом лимфоузлов [69][70][71][72][73], что не позволяет однозначно судить о роли HIF-1a в метастазировании РШМ. В то же время, многие исследователи отмечают сильную отрицательную корреляцию уровня экспрессии HIF-1a с общей/безрецидивной выживаемостью больных РШМ, ответом на первичную радиотерапию и вероятностью рецидива, на основании чего предлагается рассматривать HIF-1a как независимый прогностический фактор [70,[74][75][76].…”
Section: транскрипционные факторы: фактор индуцированный гипоксией-1unclassified
“…Previous attempts to determine the prognostic significance of the presence or absence of detectable HPV dna and hpV types in cervical cancer patients have generated conflicting results (6)(7)(8)(9)(10)(11)(12)(13). Some studies have reported that patients infected with HPV-18 had worse prognoses and higher disease recurrence rates than patients with hpV-16 infection (6)(7)(8)10). In a recent study, infection with multiple hpV types was also considered an indicator of poor response to radiotherapy (7,11).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that patients infected with HPV-18 had worse prognoses and higher disease recurrence rates than patients with hpV-16 infection (6)(7)(8)10). In a recent study, infection with multiple hpV types was also considered an indicator of poor response to radiotherapy (7,11). however, other reports did not demonstrate an association between hpV type and clinical outcome (8,9,12,13).…”
Section: Introductionmentioning
confidence: 99%